Chicken dance - Sauer, Tammi; Santat, Dan (Mascot, N.S.W. : Koala Books, 2010)
Determined to win tickets to an Elvis Poultry concert, hens Marge and Lola enter the Barnyard Talent Show, then, while the ducks who usually win the contest jeer, they test out their abilities.
Ill. on inside covers.
For children.
Keywords: Chickens -- Juvenile fiction; Domestic animals -- Juvenile fiction